The in-related self: reclaiming Paarung in critical phenomenological psychopathology - Billwiller, Elena (Frontiers in Psychology, 2025)
This article explores the conceptual and clinical implications of integrating phenomenological psychopathology with critical and feminist phenomenology. Drawing on the Husserlian concept of Paarung – understood as a passive, embodied synthesis grounding the constitution of the other – we develop a framework for interpreting perceptual disruptions in subjects affected by social oppression. After outlining the methodological foundations of phenomenological psychopathology, we show how critical approaches expand this tradition by foregrounding the socio-historical structures that shape embodied experience. To articulate the effects of power on perceptual life, we introduce the notion of malign Paarung, which designates the pathological sedimentation of social norms into embodied relationality, producing alienation and inhibiting reciprocity. The analysis focuses on two emblematic configurations: temporal disruption in racialized subjectivities (Fanon, Al-Saji) and spatial inhibition in gendered embodiment (Young, Sullivan). These are not fixed associations, but heuristic articulations aimed at clarifying how different structures of domination distort the temporal and spatial dimensions of experience in interwoven ways. The final section argues for a therapeutic appropriation of Paarung within the clinical encounter, conceived not as a neutral act of diagnosis but as a co-constitutive process capable of reorganizing disrupted experiential structures. Within this framework, relational individuation (in-related self) emerges as both an epistemological and ethical horizon of care, oriented toward the co-emergence of shared meaning and emancipatory forms of subjectivity.